Framing the Story of A Woman Politician in the Dinagat Islands, Philippines: A Post-Structural Analysis - Pavo, Raymundo R. (Animo Repository, 2019)
In this study, Bacchi and Benan’s (2016) framework is used to analyze the story of Vice Mayor Fely of Tubajon, Dinagat Islands. Her story is looked into to serve as a platform where the habits, practices, and situations in connection to structures and power relations in the political arena in her municipality and the province are brought to the fore to be in dialogue with a few critical questions. Some of these questions include: (a) Why do women politicians find it difficult to land a political position? and (b) Should women politicians be forced to carve political identities when their male counterparts are not expected to do the same? In framing the story of Vice Mayor Fely following the post-structuralist perspective, this qualitative case study presents these insights: (a) her humble beginnings is reflective of the peripheral space of women in relation to seats of power and influence, (b) her unique entry point as church volunteer points to the variety of paths for future women leaders in contrast to homogenous routes of women and men belonging to traditional political families, and (c) her story questions pervasive habits in traditional politics such as having a sense of entitlement to political positions.